Efektivitas Konseling Behavioral dengan Teknik Modeling untuk Meningkatkan Self Autonomy melalui Lesson Study - Laila, Irda; Dharsana, I Ketut; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2019)
This research aims to determine the effectiveness of behavioral counselling techniques Modeling to improve Self Autonomy through lesson study in students of class X UPW B SMK N 1 Singaraja. This type of research is research draft of Pseudo experimental population of this study is grade X students smkn 1 Singaraja. Sampling technique uses Random sampling so that the grade X student is acquired by an experimental class of 36 grade X APH A students as a control group amounting to 36 students. The method of analysis used is the ttest test and Efect Size that uses the program JASP 0.7.5.5. Data collection instruments using observations, interviews, diary and questionnaire results based on the results of this study can be recommended that this counselling model is effective to do in the process. Research shows that there is effectiveness of behavioral counseling theory with modeling technique in setting lesson study to improve Self Autonomy class X UPW students.Keywords: Self Autonomy, Behavioral Counseling, Modeling Techniques, LessonStudy